Long-term effects of BRAF inhibitors in melanoma treatment: friend or foe?. (April 2014) - Sloot, Sarah; Fedorenko, Inna V; Smalley, Keiran SM; Gibney, Geoffrey T
<x xml:space="preserve">Abstract</x> The clinical development of selective BRAF inhibitors for metastatic BRAF V600 mutant melanoma patients has been a major breakthrough in targeted therapeutics. Objective response rates of approximately 50% have been observed in the Phase III studies of the BRAF inhibitors vemurafenib and dabrafenib. The side effects can be relatively common, including proliferative skin toxicities. The latter range from hyperkeratosis and keratoacanthomas (KAs) to squamous cell carcinomas (SCCs) and new primary melanomas. In addition, case reports on the emergence of gastric/colonic polyps and RAS mutant malignancies have been described during BRAF inhibitor therapy. These events have been attributed to paradoxical activation of the MAPK pathway in BRAF wild-type cells exposed to selective BRAF inhibitors in addition to increased RAS activity. Combined BRAF and MEK inhibition appears to improve clinical outcomes and reduce cutaneous proliferation events as fewer KAs and SCCs have been observed with combination therapy. Next-generation pan-RAF inhibitors ('paradox breakers') and ERK inhibitors may further enhance clinical activity in metastatic BRAF-mutant melanoma patients and mitigate this paradoxical oncogenesis. Further investigation into the potential long-term effects of selective BRAF inhibitors is warranted as expanded use of these agents is expected in patients with BRAF-mutant melanoma and other malignancies.